Application of quantitative proteomics to discover biomarkers for tick resistance in cattle - Raza, Ali; Schulz, Benjamin L.; Nouwens, Amanda; Naseem, Muhammad Noman; Kamran, Muhammad; Mantilla Valdivieso, Emily F.; Kerr, Edward D.; Constantinoiu, Constantin; Jonsson, Nicholas N.; James, Peter; Tabor, Ala E. (Frontiers in Immunology, 2023)
Breeding for tick resistance is a sustainable alternative to control cattle ticks due to widespread resistance to acaricidal drugs and the lack of a protective vaccine. The most accurate method used to characterise the phenotype for tick resistance in field studies is the standard tick count, but this is labour-intensive and can be hazardous to the operator. Efficient genetic selection requires reliable phenotyping, such as biomarker(s), for accurately identifying tick-resistant cattle. Although breed-specific genes associated with tick resistance have been identified, the mechanisms behind tick resistance have not yet been fully characterised. This study applied quantitative proteomics to examine the differential abundance of serum and skin proteomes using samples from naïve tick-resistant and -susceptible Brangus cattle at two-time points following tick exposure. The proteins were digested into peptides, followed by identification and quantification using sequential window acquisition of all theoretical fragment ion mass spectrometry. Resistant naïve cattle had a suite of proteins associated with immune response, blood coagulation and wound healing that were significantly (adjusted P < 10- 5) more abundant compared with susceptible naïve cattle. These proteins included complement factors (C3, C4, C4a), alpha-1-acid glycoprotein (AGP), beta-2-glycoprotein-1, keratins (KRT1 & KRT3) and fibrinogens (alpha & beta). The mass spectrometry findings were validated by identifying differences in the relative abundance of selected serum proteins with ELISA. The proteins showing a significantly different abundance in resistant cattle following early and prolonged tick exposures (compared to resistant naïve) were associated with immune response, blood coagulation, homeostasis, and wound healing. In contrast, susceptible cattle developed some of these responses after prolonged tick exposure. Resistant cattle were able to transmigrate immune-response related proteins towards the tick bite sites, which may protect tick feeding. Significantly differentially abundant proteins identified in this research in resistant naïve cattle may provide a rapid and efficient protective response to tick infestation. Physical barrier (skin integrity and wound healing) mechanisms and systemic immune responses are key contributors to resistance. Immune response-related proteins such as C4, C4a, AGP and CGN1 (naïve samples), CD14, GC and AGP (post-infestation) should be further investigated as potential biomarkers for tick resistance.